Low-Fluoride Acidic Dentifrice: A Randomized Clinical Trial in a Fluoridated Area - Vilhena, F. V.; Olympio, K. P. K.; Lauris, J. R. P.; Delbem, Alberto Carlos Botazzo [UNESP]; Buzalaf, M. A. R. (Karger, 2010)
Background: Low-fluoride dentifrices have been suggested as alternatives to reduce dental fluorosis risk, but there is no consensus regarding their clinical effectiveness, which has been suggested to be increased when their pH is acidic. Aims: This single-blind randomized clinical trial evaluated the caries increment during the use of a low-fluoride acidic liquid dentifrice. Methods: Four-year-old schoolchildren (n = 1,402) living in a fluoridated area (0.6-0.8 ppm F) were randomly allocated to 4 groups differing according to the type of dentifrice used over a 20-month period. Group 1 (n = 345): liquid dentifrice, 1,100 ppm F, pH 4.5. Group 2 (n = 343): liquid dentifrice, 1,100 ppm F, pH 7.0. Group 3 (n = 354): liquid dentifrice, 550 ppm F, pH 4.5. Group 4 (n = 360): toothpaste, 1,100 ppm F, pH 7.0. At baseline and after 20 months, clinical examinations were conducted (dmfs index) and caries increment was calculated. Data were analysed by GLM procedure using classrooms (cluster) as unit of analysis (p < 0.05). Results: The mean +/- SD (95% CI) net increments found were as follows. Group 1: 2.06 +/- 2.38 (1.8-2.3); group 2: 2.08 +/- 2.87 (1.7-2.4); group 3: 2.05 +/- 2.79 (1.7-2.4), and group 4: 2.08 +/- 2.34 (1.8-2.4). No significant differences were detected among the groups. Conclusion: In a population with high caries risk living in a fluoridated area, as the selected sample, and according to the present protocol, the low-fluoride acidic liquid dentifrice seems to lead to similar caries progression rates as conventional 1,100 ppm F toothpaste. Copyright (C) 2010 S. Karger AG, Basel
Keywords: Acidic dentifrice; Dental caries; Low-fluoride dentifrice; Randomized clinical trial